STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DI ERA KURIKULUM MERDEKA - Amelia, Maria; Oktarina, Nina; Rokhman, Fathur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research examines the leadership strategies of school principals in the era of the Merdeka curriculum. The school principal as the highest leader in the school has an important role in curriculum implementation. This research aims to discuss the core of the Merdeka curriculum, the concept of strategy, the principal's leadership strategy. this research can be classified in educational management research. the method used in this research is a qualitative method with a literature review as a research reference. The research steps use the Arksey and O'Malley technique, namely identifying research questions, identifying relevant studies, selecting studies, mapping data, compiling and reporting results. The results found that the principal's strategy in the Merdeka curriculum era fo-cuses on improving school resources, which consists of improving teacher competence and managing school funds. This is done to achieve the goal of improving the quality of learning which has an impact on the quality of students.